Mierzenie międzynarodowego poziomu zatrudnienia i wzrostu. Podejście Fundacji Bertelsmanna - Suntum, Ulrich van (Benchmarking International Employment and Growth Performance. The Bertelsmann Foundation Approach, 2006)
The paper starts with presenting a general methodology of the Bertelsmann Business Location Ranking. This methodology was a background for analyzing the economic performance of twenty one OECD countries during the 1986-2003 period. The author explains, in particular, that the ranking concerned does not only reflects economic performance of investigated countries but tries to explain, with the help of the so called activity index, why some countries perform better the others. Against this background, the author discusses the economic performance of German economy over the period concerned, comparing it with the performance of other countries being subject to the Bertelsmann Business Location Ranking. The paper is supplemented with presenting the results of recent study (2004) by the Bertelsmann Foundation on the economic performance of Eastern European countries with special attention being paid to eight new EU member states.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1138, s. 81-89